Enantio‐ and Diastereoselective Hydrofluorination of Enals by N‐Heterocyclic Carbene Catalysis. Issue 22 (25th April 2019) - Wang, Leming; Jiang, Xinhang; Chen, Jiean; Huang, Yong
Abstract: In contrast to well‐established asymmetric hydrogenation reactions, enantioselective protonation is an orthogonal approach for creating highly valuable methine chiral centers under redox‐neutral conditions. Reported here is the highly enantio‐ and diastereoselective hydrofluorination of enals by an asymmetric β‐protonation/α‐fluorination cascade catalyzed by N‐heterocyclic carbenes (NHCs). The two nucleophilic sites of a homoenolate intermediate, generated from enals and an NHC, are sequentially protonated and fluorinated. The results show that controlling the relative rates of protonation, fluorination, and esterification is crucial for this transformation, and can be accomplished using a dual shuttling strategy. Structurally diverse carboxylic acid derivatives with two contiguous chiral centers are prepared in a single step with excellent d.r. and ee  values. Abstract : Rate control : Reported here is the highly enantio‐ and diastereoselective hydrofluorination of enals by an asymmetric β‐protonation/α‐fluorination cascade catalyzed by N‐heterocyclic carbenes (NHCs). The two nucleophilic sites of a homoenolate intermediate are sequentially protonated and fluorinated. Controlling the relative rates of protonation, fluorination, and esterification is crucial for this transformation.